2012
DOI: 10.1017/s0950268812002567
|View full text |Cite
|
Sign up to set email alerts
|

Testing for Chlamydia trachomatis: time trends in positivity rates in the canton of Basel-Stadt, Switzerland

Abstract: SUMMARYNational health statistics report a 2·5-fold increase in laboratory-confirmed Chlamydia trachomatis (CT) cases over the last decade in Switzerland where no CT screening programme exists. We obtained essential denominator information to describe the epidemiology of CT in the canton of Basel-Stadt, an urban canton in north-western Switzerland. Laboratories reporting at least two CT infections from Basel-Stadt residents to the SFOPH in 2010 provided demographic and test-related data. CT positivity rates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
(27 reference statements)
2
7
0
Order By: Relevance
“…The positivity rate for CT found in our analysis is consistent to what was found in another study in the Swiss cantons of Valais and Vaud [13], but slightly lower to what was found in the canton of Basel-Stadt [14], where the CT positivity rates were 4.7% and 11.2% for female and male samples, respectively. CT rates were found to be variable according to country, gender, age, and the degree of screening coverage [15], ranging from 3% (United Kingdom) to 5% (Slovenia) among women and 0.4% (Germany) to 5% (Slovenia) among men in a literature review published by the European Centre for Disease Prevention and Control [15].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The positivity rate for CT found in our analysis is consistent to what was found in another study in the Swiss cantons of Valais and Vaud [13], but slightly lower to what was found in the canton of Basel-Stadt [14], where the CT positivity rates were 4.7% and 11.2% for female and male samples, respectively. CT rates were found to be variable according to country, gender, age, and the degree of screening coverage [15], ranging from 3% (United Kingdom) to 5% (Slovenia) among women and 0.4% (Germany) to 5% (Slovenia) among men in a literature review published by the European Centre for Disease Prevention and Control [15].…”
supporting
confidence: 91%
“…CT rates were found to be variable according to country, gender, age, and the degree of screening coverage [15], ranging from 3% (United Kingdom) to 5% (Slovenia) among women and 0.4% (Germany) to 5% (Slovenia) among men in a literature review published by the European Centre for Disease Prevention and Control [15]. The peak of CT infection in terms of age groups was consistent among studies [13][14][15] and similar to our data. The rate of NG co-infection with CT was similar to other publications [5,6], but it is known to vary considerably, depending on the setting and the background prevalence of these STIs.…”
supporting
confidence: 89%
“…Chlamydia seroprevalence in pigs, cattle, dogs, cats and humans has been widely reported throughout the world [8][9][10][11][12][13][14][15], but there is limited information about Chlamydia infection in parrots available, and no such information is available for parrots in China. In this survey, we investigated the seroprevalence of Chlamydia infection in budgerigars, lovebirds, cockatiels and Alexandrine parakeets in Beijing and Weifang cities, north China, and determined the genotype of Chlamydia shed in faeces from these popular pet birds.…”
Section: Introductionmentioning
confidence: 99%
“…We use the term positivity as the rate of number of positive tests to the total number of tests performed for STEC [ 15 , 16 ]. Positivity was calculated for different demographic groups, test methods, spatial (i.e.…”
Section: Methodsmentioning
confidence: 99%